Prevalence of Morphometric Vertebral Fractures in Patients With Type 1 Diabetes - Volha V. Zhukouskaya; Cristina Eller-Vainicher; Volha Vadzianava; Alla Shepelkevich; Irina V. Zhurava; Galina Korolenko; Olivier Salko; Elisa Cairoli; Paolo Beck‐Peccoz; Iacopo Chiodini (2013)
Several studies showed low bone mineral density (BMD) and elevated risk of symptomatic fractures in patients with type 1 diabetes (T1D). To our knowledge, there has been no investigation on the prevalence of asymptomatic vertebral fractures (VFx) in T1D. In the current study, we assessed BMD and the prevalence of VFx in T1D.We evaluated 82 T1D patients (26 males and 56 females, aged 31.1 ± 8.6 years, BMI 23.5 ± 3.3 kg/m(2), disease duration 12.8 ± 8.3 years) and 82 controls (22 females and 60 males, aged 32.9 ± 5.8 years, BMI 23.9 ± 4.8 kg/m(2)). Spinal and femoral BMD (as Z-score, Z-LS and Z-FN, respectively) and the prevalence of VFx were evaluated by dual X-ray absorptiometry.T1D patients had lower Z-LS and Z-FN than controls (-0.55 ± 1.3 vs. 0.35 ± 1.0, P < 0.0001, and -0.64 ± 1.1 vs. 0.29 ± 0.9, P < 0.0001, respectively) and a higher prevalence of VFx (24.4 vs. 6.1%, P = 0.002). Age, diabetes duration, age at diabetes manifestation, glycosylated hemoglobin, Z-LS, Z-FN, and the prevalence of chronic complications were similar for patients with and without VFx. In the logistic regression analysis, the presence of VFx was associated with the presence of T1D but not with lumbar spine BMD. Whereas moderate or severe VFx was associated with low lumbar spine BMD in the whole combined group of T1D patients and controls, there was no association between moderate or severe VFx and lumbar spine BMD in the T1D group.T1D patients have low BMD and elevated prevalence of asymptomatic VFx, which is associated with the presence of T1D independently of BMD.